2011
DOI: 10.1016/j.biopsych.2011.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Magnetic Mismatch Field Latency: A Biomarker for Language Impairment in Autism

Abstract: Background-Auditory processing abnormalities are frequently observed in Autism Spectrum Disorders (ASD), and these abnormalities may have sequelae in terms of clinical language impairment (LI). The present study assessed associations between language impairment and the amplitude and latency of the superior temporal gyrus magnetic mismatch field (MMF) in response to changes in an auditory stream of tones or vowels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
151
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(171 citation statements)
references
References 43 publications
19
151
0
Order By: Relevance
“…Reports have indicated that the ASD population exhibits elevated rates of brain stem or peripheral hearing dysfunction [13][14][15][16][17][18][19][20] and abnormalities in AEF components (i.e., cortical dysfunction) [1][2][3][4][5][6][7][8][9][10][21][22][23][24][25]. Intriguingly, research has indicated that individuals with ASD may present with peripheral auditory asymmetry [13], which may distort the cortical bilateral synchronization of AEF components in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reports have indicated that the ASD population exhibits elevated rates of brain stem or peripheral hearing dysfunction [13][14][15][16][17][18][19][20] and abnormalities in AEF components (i.e., cortical dysfunction) [1][2][3][4][5][6][7][8][9][10][21][22][23][24][25]. Intriguingly, research has indicated that individuals with ASD may present with peripheral auditory asymmetry [13], which may distort the cortical bilateral synchronization of AEF components in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Altered auditory processing systems in children with ASD have been studied as neurological correlates of some phenotypes in ASD, such as inhibited language acquisition [1][2][3][4][5][6][7][8] and auditory hypersensitivity [9][10][11], and previous studies that have focused on auditory responses of the brain have also demonstrated altered cerebral laterality [2,5,6] and regional connectivity [12] in children with ASD. These studies have indicated alterations in cortical auditory processes in ASD [1,2,4,5,9,10], whereas increased rates of brain stem or peripheral hearing dysfunction have also been reported in the ASD population [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MEG has also received increasing acceptance as a superb non-invasive tool for localizing eloquent cortices in presurgical www.intechopen.com functional brain mapping in patients with tumors and other operable lesions (Burgess, Barkley, et al 2011). Further efforts of the MEG community are focused on establishing new clinical indications where dementia (Zamrini et al 2011), traumatic brain injury (TBI) (Huang et al 2009;Maruta et al 2010) and autism (Roberts et al 2011;Roberts et al 2010) are considered current front runners among many other neurologic and psychiatric disorders that are being studied (Stufflebeam et al 2009;C. Stam 2010).…”
Section: Applications Of Real-time Meg In Neurology and Neurosurgerymentioning
confidence: 99%